Такого неба нет нигде: стихи и проза / Александра Дарьина ; [художник Е. Чуркина] - Дарьина Александра Петровна (Нефтяник, 2005)
Экземпляры: аб. ДБ (2017.20.12) / Инвентарный номер: 3847 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 20 / ББК: 84(2Рос=Рус)6